2017
DOI: 10.18203/2320-1770.ijrcog20172305
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal multivitamin supplementation increases birth weight

Abstract: Background: The aim of this study is to examine whether there is any positive impact of prenatal iron and vitamin supplementation on birth weight, and if this practice could be a cause of macrosomia.Methods: A total of 1,838 term pregnant women were included in this study and were divided into four groups: iron group (women having only iron supplementation), vitamin (women using only multivitamins), vitamin+iron (women using both iron and multivitamin preparations), and control group (women having neither iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…Aside from its relationship with NT, the present study identified a positive correlation between birthweight and maternal weight gain, and a negative correlation with smoking, and both of these findings are consistent with literature (28,29,30) .…”
Section: Discussionsupporting
confidence: 92%
“…Aside from its relationship with NT, the present study identified a positive correlation between birthweight and maternal weight gain, and a negative correlation with smoking, and both of these findings are consistent with literature (28,29,30) .…”
Section: Discussionsupporting
confidence: 92%